PERAN POSITIVISME HUKUM DALAM PENEGAKAN KODE ETIK DAN HUKUM DI INDONESIA - Dzikri Ubaydilah; Muhammad Irvan Zidni Al Hakim (JURNAL ILMIAH NUSANTARA, 2025)
The law needs morals, Quid leges sine moribus? (What does Law without morality mean?). The quality of the law is also measured by its moral quality. On the other hand, morality also needs law. Law enforcement in Indonesia today is based on legal positivism that emphasizes compliance with legal norms. The code of ethics is related to this, which functions as the main guideline in maintaining morals and supervising the behavior of professional members. With the existence of a code of ethics, each member of the profession has a clear reference regarding the principles that must be followed in carrying out their work. These rules not only aim to ensure that each member of the profession acts in accordance with the standards that have been set, but also helps to create an ethical and responsible work environment.